Pantomime as a Foundation for Ritual and Language - Gärdenfors, Peter (Studia liturgica, 2018)
This article aims at tracing the evolutionary roots of rituals. My main thesis is that rituals have emerged as conventionalizations of pantomimes. The original function of pantomime is for teaching. In that function, pantomime derives from demonstration. My focus in this article is on rituals that produce group identification. Like pantomime, rituals signify meaning beyond the actual actions. Like demonstration and pantomime, ritual is a tool for learning. What is learnt is system of beliefs that become shared within a society. Such shared beliefs strengthen the cohesion within a society. Although both ritual and language are tools for sharing worlds, they have partly different functions. One function of ritual is to promote long-term cooperation, while language primarily coordinates action.